1998
DOI: 10.4315/0362-028x-61.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Multiplex PCR System for the Simultaneous Detection of Heat Labile Toxin I and Heat Stable Toxin II Genes of Enterotoxigenic Escherichia coli in Skim Milk and Porcine Stool

Abstract: Enterotoxigenic Escherichia coli (ETEC) strains which produce heat labile and/or heat stable toxins (LT and ST) may cause diarrhea in humans and farm animals. Using PCR primers specific for the LT I and ST II genes, a multiplex PCR system which allows detection of LT 1-and ST 11-producing ETEC strains was developed. When skim milk was used for a PCR assay, it was found that if target cells in the sample were precultured in MacConkey broth for 8 h prior to PCR as few as 10(0) cells per ml of the sample could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In addition to these, EHEC strain was not detected in any farms that were contaminated with E. coli ( Table 2). This observation is consistent with previous reports claiming that enterotoxigenic E. coli strains that are lt2+ are rarely found [17], and so far, ETEC strains that are lt2+ have been isolated only in Brazil, Thailand and [7,8,18,19]. Roy et al [8] were able to identify the virulent strains lt2 genes of ETEC group and EAE gene of EPEC group from shrimp farms.…”
Section: Pcr Analysis Of Water Sediment Of Shrimp Farms and Shrimp Ssupporting
confidence: 81%
See 1 more Smart Citation
“…In addition to these, EHEC strain was not detected in any farms that were contaminated with E. coli ( Table 2). This observation is consistent with previous reports claiming that enterotoxigenic E. coli strains that are lt2+ are rarely found [17], and so far, ETEC strains that are lt2+ have been isolated only in Brazil, Thailand and [7,8,18,19]. Roy et al [8] were able to identify the virulent strains lt2 genes of ETEC group and EAE gene of EPEC group from shrimp farms.…”
Section: Pcr Analysis Of Water Sediment Of Shrimp Farms and Shrimp Ssupporting
confidence: 81%
“…Roy et al [8] were able to identify the virulent strains lt2 genes of ETEC group and EAE gene of EPEC group from shrimp farms. In the current experiment, the PCR was performed without screening and removing detritus to avoid target loss [17] and to reduce extra time needed assuming that PCR is able to amplify target DNA if present in the sample. Overall, the PCR analyses confirmed that st1+, lt2+ (of ETEC origin) and vt+ E. coli strains were present in water, sediment and shrimp samples of unhygienic farms.…”
Section: Pcr Analysis Of Water Sediment Of Shrimp Farms and Shrimp Smentioning
confidence: 99%
“…Relevant techniques include use of PCR and/or hybridization probes to detect E. coli-specific genes encoding invasion proteins (12,13), toxins (17,23,24), catabolic enzymes (4,8), or structural (lipo)proteins (10,12). A drawback to these approaches has been that when cross-reactivity tests were done, target sites were often detected not only in E. coli but also in closely related organisms (14,17,18).…”
mentioning
confidence: 99%
“…ETEC, an important cause of travelers' diarrhea and infantile diarrhea, is detected by mPCR by targeting the genes that encode the ETEC enterotoxins, LT (heat-labile enterotoxin) and ST (heat-stable enterotoxin). Tsen et al (1998) developed an mPCR assay specific for eltA (heat-labile enterotoxin subunit A) and the porcine variant of estA (heat-stable enterotoxin) for detection of ETEC in porcine stool and feed samples. Grant et al (2006) used primer-TaqMan probe sets targeting eltB and both human and porcine variants of estA to detect ETEC in raw vegetables, water and salsa.…”
Section: Single-pathogen Detection By Mpcrmentioning
confidence: 99%